2016
DOI: 10.1074/jbc.m116.730697
|View full text |Cite
|
Sign up to set email alerts
|

The Kinesin-5 Chemomechanical Cycle Is Dominated by a Two-heads-bound State

Abstract: Single-molecule microscopy and stopped-flow kinetics assays were carried out to understand the microtubule polymerase activity of kinesin-5 (Eg5). Four lines of evidence argue that the motor primarily resides in a two-heads-bound (2HB) state. First, upon microtubule binding, dimeric Eg5 releases both bound ADPs. Second, microtubule dissociation in saturating ADP is 20-fold slower for the dimer than for the monomer. Third, ATPtriggered mant-ADP release is 5-fold faster than the stepping rate. Fourth, ATP bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
58
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 60 publications
(46 reference statements)
11
58
0
Order By: Relevance
“…At limiting ADP concentrations the MT unbinding rate is near zero (confirming that the apo-state binds tightly), and at saturating ADP concentrations the MT unbinding rate plateaus; the ADP concentration at which the rate is half-maximal represents the K D for ADP binding to the Eg5-MT species 40 (see Figure 3c inset). Under control conditions, Eg5 had a maximal MT-unbinding rate of 0.55 ± 0.02 s −1 and an ADP affinity of K D ADP = 86 ± 7 μM ADP (Figure 3c), in agreement with previous work 14 . In the presence of BRD9876, the effective nucleotide affinity dropped 25-fold (K D apparent = 2.2 ± 1.1 mM ADP), while the maximal off-rate remained at 0.52 ± 0.18 s −1 (Figure 3c).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…At limiting ADP concentrations the MT unbinding rate is near zero (confirming that the apo-state binds tightly), and at saturating ADP concentrations the MT unbinding rate plateaus; the ADP concentration at which the rate is half-maximal represents the K D for ADP binding to the Eg5-MT species 40 (see Figure 3c inset). Under control conditions, Eg5 had a maximal MT-unbinding rate of 0.55 ± 0.02 s −1 and an ADP affinity of K D ADP = 86 ± 7 μM ADP (Figure 3c), in agreement with previous work 14 . In the presence of BRD9876, the effective nucleotide affinity dropped 25-fold (K D apparent = 2.2 ± 1.1 mM ADP), while the maximal off-rate remained at 0.52 ± 0.18 s −1 (Figure 3c).…”
Section: Resultssupporting
confidence: 91%
“…To analyze the mean-square displacement (MSD), either a quadratic form ( MSD(Δt) = v 2 Δt 2 + 2DΔt + σ 2 ) or a linear form ( MSD(Δt) = 2DΔt + σ 2 ) was assigned based on the presence or the absence of stepping. In saturating ATP, the motor had a velocity of 66 ± 26 nm/s and a negligible diffusion coefficient of 594 ± 167 nm 2 /s, consistent with our previous findings that Eg5 dimers step processively in ATP 14 . In contrast, in saturating ADP the motor diffused along the microtubule with D = 3,845 ± 119 nm 2 /s.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Dimeric Eg5(513) is characterized by its low processivity (∼70 nm) and speed (< 100 nm/s). Previous works also showed that the stall force of this motor [35,51] and the kinetic constants of disociation from and association to microtubules [5254] are similar to those of kinesin-1.…”
Section: Resultsmentioning
confidence: 70%